The Effect of Brand Image and Somethinc's Product Prices on Customer Loyalty with Customer Satisfaction as Intervening Variable - Sinaga, Inggrid Wahyuni; Robi'ah, Putri (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aims to analyze the relationship between brand image and price and how it affects customer loyalty for Somethinc products and customer satisfaction as intervening variable. This study uses a quantitative approach, collecting primary data via questionnaires using survey methods. In the research sampling, the purposive sampling technique was used. A total of 200 people who used Somethinc product made up the research sample. The Smartpls application was then used to evaluate the survey data using the SEM-PLS analysis technique. According to the study's findings, brand image and price affect customer satisfaction, but brand image have no bearing on customer loyalty. Price and customer satisfaction, on the other hand, have an affect on consumer loyalty. Additionally, this study's findings show that customer satisfaction is proven to be able to mediate the indirect effect of brand image and price on Somethinc's customer loyalty